In vitro Anthelmintic activity of Aralia racemosa. L (root) and Argyreia Pilosa Wight & Arn. (Whole plant) against Pheretima Posthuma: In-vitro Anthelmintic Potential of Aralia racemosa. L and Argyreia pilosa Wight & Arn - D. S. N. B. K., Prasanth; Rao Atla, Srinivasa; Prasad Atla, Rajendra (Iranian Journal of Pharmaceutical Sciences, 2021)
To carry out a thorough study to establish the therapeutic of methanolic and aqueous extract of root of Aralia racemosa and whole plant of Argyreia pilosa against Pheretima posthuma, which is utilized as an experimental model for helminthic. The Aralia racemosa (Root), Argyreia pilosa (whole plant), and Indian adult earthworms (Pheretima posthuma) were collected and identified by an approved taxonomist. Earthworms had been grouped and treated with extracts at a concentration of 10, 20, 40, and 80mg/mL; albendazole of 40mg/mL as standard and normal saline as a control. The paralysis and death time was regarded as an indicator of anthelmintic activity. Crude methanolic and aqueous extracts with concentrations of 10, 20, 40, and 80mg/ml of A. racemosa and A. pilosa showed concentration-dependent activity, but significant activity was observed at 80 mg/mL in both of the plants. The methanolic extract showed better activity than aqueous extracts at all concentrations. The methanolic extract of A. racemosa [P (min) = 2.01, D (min) = 10.52] and A. pilosa [P (min) = 2.45] respectively, the activity was found to be equivalent as compared to the standard drug Albendazole [P (min) = 2.28, D (min) = 5.44]. From the investigation, a conclusion can be drawn that methanolic extracts showed better activity than aqueous extracts of A. racemosa and A. pilosa to treat intestinal worm infections. Since this is a preliminary evaluation, isolation of chemical constituents that are responsible for the activity could be done in the future